Media Bangun Ruang Bambu Untuk Meningkatkan Hasil Belajar Matematika - Rusali, Ebit (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study aims to determine the effectiveness of the use of bamboo building media in an effort to improve student learning achievement in building material on the flat side. This study was conducted with experimental methods in the category of Pre-test-Post-test Control Group Design. This study selected two groups, namely class experiment and control class. Learning carried out in the experimental group using teaching aids is the media that builds the Bamboo room while the control group teaches the teaching process using the conventional (normal) method. The results of the t test show that the average scores of the experimental class and the control class post-test are very significant differences. This means that the use of Bamboo Beams media has an effectiveness towards improving student learning outcomes.